Stiffness loss of laminates with aligned intralaminar cracks Part I. Macroscopic constitutive relations (Archives of Mechanics - Test, 1996)
The paper deals with analysis of reduction of the in-plane effective elastic moduli of the [0°m/90°n] laminates weakened by aligned cross-cracks in the 90°-layer. A regular crack pattern is assumed. The case of dense crack distribution is modelled by (h0, l0) approach, while the case of arbitrary crack density cd is described by a more accurate model (h0, l). Both models have been derived in our paper [10]. Closed-form formulae describing decaying curves E1(cd), E2(cd), ν12(cd), ν21(cd), G12(cd) are found by solution of the local problems for both models.